"What if?": Addressing uncertainty with families. Issue 6 (8th March 2019) - Snaman, Jennifer M.; Feraco, Angela M.; Wolfe, Joanne; Baker, Justin N.
Abstract: Children with cancer and their families deal with uncertainty throughout their treatment course. Clinicians must help patients and families manage uncertainty by engaging them in discussions about their worries and fears. Too often, clinicians avoid or defer discussions about anticipated or worried‐about future events—the "what ifs." Failing to engage in these conversations may lead to increased distress. We have developed a framework for having "what if" conversations with patients and families that enables providers to explore families' informational and emotional needs. This framework may enable providers to improve families' prognostic understanding, explore concerns, and examine preferences and goals of care.